﻿Measuring medication adherence of hypertensive patients with monotherapy treatment in a community health center by utilizing medication possession ratio - Irma Melyani Puspitasari; Laila Nur Azizah; Rano Kurnia Sinuraya; Sofa Dewi Alfian; Rizky Abdulah (Pensoft Publishers, 2022)
Adherence is a particular concern in treating hypertension, and non-adherence to antihypertensive drugs might cause uncontrolled hypertension. This study aimed to measure retrospectively the medication adherence of hypertensive patients with monotherapy treatment in a community health center (Puskesmas) in Bandung city, Indonesia. The retrospective patient data from 2011 to 2015 were obtained from an electronic prescription database. The patient data of those diagnosed with hypertension, >18 years old, and who received mono-antihypertensive therapy within a 12-month period were included in this study. To assess medication adherence, the medication possession ratio (MPR) was applied. Out of 780 patients, 93.6% of patients showed poor adherence, about 5.8% showed intermediate adherence, and 0.6% of patients had high adherence. Males and females showed different levels of adherence (p<0.05). Efforts should be focused on obtaining optimum clinical benefits and strengthening the effectiveness of health systems in Indonesia.